Do We Abuse Drugs? Reports of Social Studies and Early Childhood Education Student-Teachers in two Nigerian Colleges of Education - Yomi, Oladimeji Kolawole; Adewale, Amosun Peter; Kayode, Olowe Peter (International Journal of Social Learning (IJSL), 2022)
The study investigated the incidence of drug abuse among student-teachers in two Nigerian colleges of education. The study’s population comprised all NCE II and III Social Studies and Early Childhood Education student-teachers in two colleges located in Oyo State, Nigeria. Data was analysed using frequency counts, percentage, mean and standard deviation. Of the 400 student-teachers, 213(53.3%) were male while 187(46.8%) were female. Only 148(37%) were from Early Childhood Education while 252(63%) were from Social Studies. The student-teachers may exert negative influence on young children when they eventually take up appointment as teachers in pre-primary and primary schools. Departments of Social Studies and Early Childhood Education together with the colleges counseling centers should organize regular counseling activities and services to educate the pre-service teachers about the danger and implications that could result from their involvement in abuse of drugs.